please answer with clear instructions so that i can apply this to other equations
![please answer with clear instructions so that i can apply this to other equations class=](https://us-static.z-dn.net/files/d0b/58a04dde7f0acb840a1d27c4828bfbd2.jpg)
Answer:
x = 0.5
Step-by-step explanation:
2x - 3 = - 2 ( add 3 to both sides )
2x = 1 ( divide both sides by 2 )
x = [tex]\frac{1}{2}[/tex] = 0.5
Answer:
x = 0.5
Step-by-step explanation:
Okay, let's start with writing down the equation:
2x - 3 = -2
Now, you can move the - 3 to the other side, and when you change the side, you change the sign, meaning the new sign for that would be positive.
2x = 3 - 2
2x = 1
Now, you have to divide both sides by 2, so you can get the x alone.
x = 0.5